Manajemen Pemasaran Sayur Organik (Studi Kasus pada P4S Eka Setia Lestari di Desa Bangli, Kecamatan Baturiti, Kabupaten Tabanan) - PUTU SURYA DHARMA PUTRA; I GUSTI AGUNG AYU AMBARAWATI; RIA PUSPA YUSUF (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2015)
Abstract Organic Vegetable Marketing Management (A Case Study in P4S Eka Setia Lestari at the Bangli Village, Sub-District of Baturiti, Regency of Tabanan). This study aimed to determine the organic vegetable marketing management, from the aspect of the marketing mix and the constraints faced by the P4S Eka Setia Lestari in Bangli village, Baturiti Sub-District, Tabanan. The choice of location of the research was conducted by the purposive method, with the consideration that this group has obtained organic certification from LeSOS. The data in this study were obtained through a survey to the members of P4S Eka Setia Lestari and in-depth interviews with key informants. The analysis in this study was a qualitative descriptive method with emphasis on planning, implementation, marketing management, and supervision. P4S Eka Setia Lestari produces 21 kinds of vegetables. Marketing channels used were the direct marketing to consumers. Promotion was conducted by advertising. Constraints faced in the implementation of the current marketing management from the aspect of the product, was still facing obstacles namely it still depends on customer orders, production processes which require more time, so difficult to get a customer because organic more expensive, the obstacles encountered were the lack of an effective lines to send the product to the consumer, the constraints faced were the lack of use of technologies such as the internet and the limited budget in organizing exhibitions independently as well as promoting the organic vegetable products through mass media. Keywords: Organic Vegetables, Marketing Management, Marketing Mix.